Modification and Nutritional Outcome of Food High-Protein at Sinta Rangkang Nursing Home - Dewi, Fretika Utami; Sugiyanto, Sugiyanto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
-